The journey to the past of the National Archives of the Philippines a beacon for its future - Ignacio, Daphne D.; Aguirre, Vyva Victoria M.; Tarlit, Rodolfo Y.; Rey, Emma M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
This study utilizes the historical method of research to come up with a comprehensive history of the National Archives of the Philippines (NAP). More than just enumerating and identifying the chronological order of events, this paper also tried to identify the socio-cultural factors that have a hand in the growth and development of this institution. It is through identifying these events that one can fully comprehend the present state of NAP. It is also hoped that by gaining a better understanding of the nature of this institution and identifying the root of its problems, its administration will be more informed in coming up with the necessary measures to remedy the ills that have been identified.
These socio-cultural factors that were perceived as influential in shaping this institution were grouped into four. The first group is labeled as Culture which covers the colonial past, written culture, ecclesiastical practices and the educational system of the country. The second group is labeled as Filipino people which covers the public's perceived value of the National Archives of the Philippines and their historical memory. The third group is labeled as Philippine Government. This considers the role played by the different branches of the government namely, executive branch, legislative branch, judicial branch. The discussion regarding the NAP employees will also fall into this third category. The fourth group is labeled as Hazards and Disasters (Natural or Man-made). This explores the effects of the natural calamities such as typhoons, floods, earthquakes, El Nino and La Nina phenomenon on state of this archival institution. One of the greatest man-made hazards that have caused considerable damage on this archival institution was war.
The study also showed that to some extent, all these socio-cultural factors are always present in a given period. This is because they are all interconnected with each other. However, the extent of their influence on the institution varies in a given period with one or two factors being more dominant than the others.
As this institution tries to achieve the mission and vision that it had set for itself, it continues to seek for ways toward this end. A step closer to its goal was achieved through the enactment of Rep. Act No. 9470. This act was envisioned to strengthen this institution and to provide for a legal basis, among others, for the measures that need to be implemented to resolve the identified problems that have plagued this institution for such a long time. As to how effective this law is, remains to be seen. Nevertheless, one can just continue to hope that indeed, this will mark the beginning of the period filled with positive changes and progress.
Vita.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: National Archives of the Philippines; Philippines. National archives of the Philippines Act of 2007.; Philippines -- Archival resources -- Law and legislation